The Practice of Christian Life in “Ojcze nasz” by August Cieszkowski - Kaszyca, Marek (Hybris, 2024)
In the paper I show the ethical and religious dimension of the treatise Ojcze nasz (Eng. Our Father) by August Cieszkowski. First, practice was considered as the basic criterion for accepting or rejecting faith (its impact on human life). Then, the definition of faith was developed as three relationships (to God; to oneself; to others) in the context of Cieszkowski’s critical comments on the lifestyle of Christians of that time. Finally, I bring out the religious motivation of Cieszkowski’s philosophy, his deep concern for the implementation of the Christian principle of following Jesus in life trough social act.